2022
DOI: 10.1155/2022/2630351
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 80 Promotes Migration and Invasion of Non-Small Cell Lung Cancer Cells by Regulating the TGF-β/SMAD Pathway

Abstract: Upregulation of keratin 80 (KRT80) expression levels and carcinogenic function has been found in several types of tumors. However, its contribution and mechanism in NSCLC remain to be outlined. In this study, bioinformatic investigation from the TCGA dataset revealed that KRT80 was confirmed to be elevated in human NSCLC tissues. The results of qRT-PCR and Western blot assays disclosed that KRT80 was uplifted in NSCLC cells. Data from CCK-8 and colony formation assays exhibited that depletion of KRT80 restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, KRT80 knockdown was reported to inhibit proliferation, anti-apoptosis, anti-pyroptosis, migration, invasion, and epithelial- mesenchymal transition (EMT) in gastric cancer cells. 10 Tong et al 14 found that depletion of KRT80 restrained proliferation, migration, invasion, and EMT of lung cancer cells by affecting the TGF-β/SMAD pathway. Liu et al 12 found that miR-206/ETS1-mediated KRT80 overexpression promoted the proliferation, the transition from G 1 phase to S phase, invasion, migration and EMT of ovarian cancer cells by MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KRT80 knockdown was reported to inhibit proliferation, anti-apoptosis, anti-pyroptosis, migration, invasion, and epithelial- mesenchymal transition (EMT) in gastric cancer cells. 10 Tong et al 14 found that depletion of KRT80 restrained proliferation, migration, invasion, and EMT of lung cancer cells by affecting the TGF-β/SMAD pathway. Liu et al 12 found that miR-206/ETS1-mediated KRT80 overexpression promoted the proliferation, the transition from G 1 phase to S phase, invasion, migration and EMT of ovarian cancer cells by MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The GO term ‘cell differentiation’ includes TBL1X/Y related 1 ( TBL1XR1 ), and in NSCLC cells, TBL1XR1 has been shown to promote cell survival, proliferation, and metastasis [ 64 ]. The GO term ‘cytosol’ includes Keratin 80, which is known to promote the migration and invasion of NSCLC cells by regulating the TGF-β/SMAD pathway [ 65 ]. The GO term ‘catalytic activity’ includes C-C motif chemokine ligand 5, which activates αvβ3 integrin to promote migration as facilitated by the PI3K/Akt pathway through the activations of IKKα/β and NF-κB pathways in NSCLC cells [ 66 ].…”
Section: Discussionmentioning
confidence: 99%